ZEB2 stably represses RAB25 expression through epigenetic regulation by SIRT1 and DNMTs during epithelial-to-mesenchymal transition - Nicolas Skrypek (Epigenetics & Chromatin, 2018)
Abstract Background Epithelial mesenchymal transition (EMT) is tightly regulated by a network of transcription factors (EMT-TFs). Among them is the nuclear factor ZEB2, a member of the zinc-finger E-box binding homeobox family. ZEB2 nuclear localization has been identified in several cancer types, and its overexpression is correlated with the malignant progression. ZEB2 transcriptionally represses epithelial genes, such as E-cadherin (CDH1), by directly binding to the promoter of the genes it regulates and activating mesenchymal genes by a mechanism in which there is no full agreement. Recent studies showed that EMT-TFs interact with epigenetic regulatory enzymes that alter the epigenome, thereby providing another level of control. The role of epigenetic regulation on ZEB2 function is not well understood. In this study, we aimed to characterize the epigenetic effect of ZEB2 repressive function on the regulation of a small Rab GTPase RAB25. Results Using cellular models with conditional ZEB2 expression, we show a clear transcriptional repression of RAB25 and CDH1. RAB25 contributes to the partial suppression of ZEB2-mediated cell migration. Furthermore, a highly significant reverse correlation between RAB25 and ZEB2 expression in several human cancer types could be identified. Mechanistically, ZEB2 binds specifically to E-box sequences on the RAB25 promoter. ZEB2 binding is associated with the local increase in DNA methylation requiring DNA methyltransferases as well as histone deacetylation (H3K9Ac) depending on the activity of SIRT1. Surprisingly, SIRT1 and DNMTs did not interact directly with ZEB2, and while SIRT1 inhibition decreased the stability of long-term repression, it did not prevent down-regulation of RAB25 and CDH1 by ZEB2. Conclusions ZEB2 expression is resulting in drastic changes at the chromatin level with both clear DNA hypermethylation and histone modifications. Here, we revealed that SIRT1-mediated H3K9 deacetylation helps to maintain gene repression but is not required for the direct ZEB2 repressive function. Targeting epigenetic enzymes to prevent EMT is an appealing approach to limit cancer dissemination, but inhibiting SIRT1 activity alone might have limited effect and will require drug combination to efficiently prevent EMT.